2017
DOI: 10.18203/2319-2003.ijbcp20174781
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational session on knowledge and attitude towards teratogenicity among undergraduate medical students: a comparative study

Abstract: Background: Teratogenicity is a major cause of abortion, still birth and can result in longterm disability with a significant impact on individuals, families, societies and healthcare systems. Drugs being one of the causes of teratogenicity, creating awareness among medical students, the future prescribing physicians, the rate of teratogenicity can be decreased. The objective was to compare the attitude and knowledge about teratogenicity among the medical undergraduates before and after an educational session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These results are consistent with the previous published studies. 18,19 Also, very few percentages of students about 33.58% knew about all the five US-FDA risk categories. Also, only 33.2% and 22.3% of students were able to mention the names of two teratogenic drugs and teartogenic defects associated with drugs respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the previous published studies. 18,19 Also, very few percentages of students about 33.58% knew about all the five US-FDA risk categories. Also, only 33.2% and 22.3% of students were able to mention the names of two teratogenic drugs and teartogenic defects associated with drugs respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the previous published studies. 18,19 When the mean knowledge score of the students after the educational intervention was compared with the mean knowledge score at pre-intervention it was found that there was a significant improvement indicating the impact of educational session and scope for improvement with the early intervention among the students.…”
Section: Discussionmentioning
confidence: 99%